ANALISIS PERAN PEMERINTAH DALAM MENINGKATKAN PEREKONOMIAN SUKU ANAK DALAM : STUDI PADA DESA LUBUK JERING KEC. AIR HITAM KAB. SAROLANGUN - Jazali, Munawir; Hardi, Eja Armaz; Nofriza, Eri (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to determine the government’s role in improving the economy of the Orang Rimba, the obstacles encountered in fulfilling the Suku Anak Dalam, and the reasons why the Orang Rimba are still isolated from life in general. This study uses qualitative research. Explain the reality of the events under study. This makes it easier for the writer to obtain data in understanding the analysis of the government’s role in improving the economy of the tribal children in. From the results of this study it can be concluded: 1. The role of the government in improving the economy of the tribal children in, namely: assistance from the government, business capital, coaching. 2. Obstacles faced by the government in improving the internal tribal economy, namely: the absence of focused organization, constraints in conducting outreach, constraints in data collection. 3. The causes of the inner tribe of children who are still isolated from outside life, namely: still following the beliefs of their ancestors, and still following the old culture and rejecting new cultures from the outside.